Peran Beban Kerja terhadap Burnout Pada Karyawan PT X - Marsha Zaki Anggraini; Rita Markus Idulfilastri (Departement of Mathematics Education, 2023)
This study aims to find out and analyze how workload influences burnout in PT X’s employees. This research is a non-experimental quantitative study and uses non-probability sampling method with a purposive sampling type involving 317 PT X’s employees. The instruments used in this study are the Maslach Burnout Inventory-General Survey (MBI-GS) to measure burnout variables and the Carga Mental Questionnaire (CarMen-Q) to measure workload variables. The analysis used is non-parametric analysis and uses Spearman rho correlation with testing through IBM SPSS Statistics version 26. The results of this study are that there is a significant effect of workload on burnout in PT X’s employees.